(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Public awareness is the mainstay to control an emerging pandemic. This study investigated the knowledge, attitudes and practices of COVID-19 among chronic disease patients during the pandemic. Materials and methods: A cross-sectional study was conducted from June-October 2021 at Chittagong Medical College Hospital, Southern Bangladesh. This study included 1537 chronic disease patients by convenient sampling using a pre-structured questionnaire. Multivariable logistic regression analyses were performed to identify factors associated with poor knowledge and practice towards COVID-19. The strength of the association between the dependent and independent variables was demonstrated by computing Odds Ratio (OR) with a 95% Confidence Interval (CI). Correlation between knowledge, attitude and practice scores were done by using Pearson correlation coefficient. p-value <0.05 was considered as statistically significant. Microsoft Xcel and SPSS version 23 was used for analysis. Results: The prevalence of poor attitude and poor practice was high (49.4%, 83.4%). Age >55 years reported poor knowledge. Educational status of “can’t read and write”, unemployment, multi-morbidity (OR= 3.06, 1.40, 2.06 with 95% CI and OR=2.95, 2.19, 2.22 with 95% CI respectively) and low monthly family income (p =<.05) were significantly associated with poor knowledge and practice. Female, married, illiterate and rural participants (OR=2.09, 2.55, 2.6, 1.3) had significant less optimistic attitude. Poor knowledge was correlated significantly with poor attitude and practice. Conclusions: Targeted health education towards the current COVID-19 pandemic, among adults with chronic diseases is necessary to reduce disease severity as well as economic burden. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 51-56